PENGARUH KETERAMPILAN MANAJERIAL KEPALA SEKOLAH, SUPERVISI AKADEMIK DAN KEPUASAN KERJA GURU TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN BREBES KABUPATEN BREBES - Nurohim; Noor Miyono; Titik Haryati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The background to this research is that teacher performance is still low. The less skilled managerial skills of school principals cause low teacher performance. Poor academic supervision also causes low teacher performance and low teacher job satisfaction can influence low teacher performance which leads to the quality of achieving educational goals. This research aims to (1) describe the influence of school principals' managerial skills on the performance of state elementary school teachers in Brebes District; (2) describe the influence of academic supervision on the performance of state elementary school teachers in Brebes District; (3) describe the influence of teacher job satisfaction on the performance of state elementary school teachers in Brebes District; and (4) describe the influence of the principal's managerial skills, academic supervision and teacher job satisfaction on the performance of state elementary school teachers in Brebes District. The population of this research was all state elementary school teachers in Brebes District, Brebes Regency, totaling 440 people, a sample of 210 teachers determined using proportional random sampling technique. The data analysis used is descriptive analysis, prerequisite tests, single regression analysis and multiple regression analysis calculated using the SPSS for Windows version 23. The research results show: (1) there is a significant influence of the principal's managerial skills on teacher performance which is expressed in the equation Y= 104.859 + 0.196X1, the strength of the correlation is 0.593 with an influence of 0.352 or 35.2%; (2) there is a significant influence of academic supervision on teacher performance which is expressed in the equation Y= 108.318 + 0.171X2, the strength of the correlation is 0.473 with an influence of 0.224 or 22.4%; (3) there is a significant influence of teacher job satisfaction on teacher performance which is expressed in the equation Y= 99.285 + 0.217X3, the strength of the correlation is 0.530 with an influence of 0.281 or 28.1%; and (4) there is a significant influence of the principal's managerial skills, academic supervision, and teacher job satisfaction together on teacher performance which is expressed in the equation Y = 80.531 + 0.210X1 + 0.233X2 + 0.651X3, the strength of the correlation between X1 and Y is equal to 0.0593, the correlation of X2 to Y is 0.473 and the correlation of X3 to Y is 0.530 with an influence of 0.678 or 67.8%. The conclusion of this research is that the principal's managerial skills, academic supervision, and teacher job satisfaction have an influence on teacher performance by 67.8%. The author suggests that the principal's managerial skills, academic supervision, and job satisfaction are determining factors for teacher performance, so school principals must take part in training to improve managerial skills, carry out academic supervision well and create job satisfaction so as to improve teacher performance.